Success Stories Developed, Indigenous Technologies Identified andInnovative Methodology Adopted by KVK Pulwama. (Indian Journal of Extension Education, 2010)
Success story is the essence of any institution in general and KVK’s in particular. It depicts the magnitude of work culture. It is a corner stone on which the edifice of income generating activities followed up with field level demonstrations, transfer of technology skills, conducting of on farm testing / trials and other related activities of a KVK is built. In fact a KVK without success stories is like a human being drained off blood. Success stories act as a catalyst in making an institution more vibrant, work oriented and people friendly. They infuse a new life in the work culture of KVK’s and make them more responsive to the needs of the people. Success stories are a gauge for measuring the amount of success a KVK has achieved in the implementation of its workprogramme.